PENGARUH KECANGGIHAN MESIN TERHADAP AKURASI UKURAN KAYU GERGAJIAN - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1989)
This  study   was  carried  out  at  a sawmill  in  Lampung,   Sumatera.   The sawmill  had  two  unit  of  band-headrigs   with different  type  of  machines,   namely  a conventional    mill  and  a modern   one.   The design of  the modern  mill is more  sophis- ticated   in  characteristics   as  figured   in  Table   1.    Accuracy    of  sawn   timber   was  determined    by  comparison    between actual  size  and  target size  of  the  lumber  thickness.   The  data  were  collected   from  measurement   of  1OO pieces  of  lumber selected  randomly   from  each mill production.The  result  showed   that  the  machine  sophistication    has a significant   effect  on sawn  timber  size accuracy.  The more sophisticated   machine   can  give  more  than  10%    benefit   of  sawn  timber  production    compared   to  the  conventional   one. The level of sawing accuracy  on conventional   mill  is 88.15%,     whereas  the  modern  mill could  reach 98.29%.